Word Learning in First Grade: Evaluating the Effectiveness of a Technology-Based and an Extended Vocabulary Intervention. Issue 4 (4th July 2021) - Loftus-Rattan, Susan M.; Furey, Jenlyn
Abstract: In this study we examine the effectiveness of a technology-based vocabulary intervention compared to an extended vocabulary intervention that has been validated in previous studies. At-risk first grade students learned new words through each condition in a within-subjects design. Comparisons of target word knowledge between the two conditions were made within each participant using a repeated measures ANOVA. Our findings indicated that students learned words to a greater degree when they were taught using the extended vocabulary condition when compared to word learning in the technology-based condition. However, students did demonstrate meaningful gains in target word knowledge in the technology-based condition. We discuss the benefits and limitations of each intervention in terms of feasibility and resource requirements.